To Study the Emergence of Mcr-1 Gene In Carbapenemase Encoding Colistin Resistance Klebsiella Pneumoniae in Clinical Isolates at a Tertiary Care Centre - Kumar, Deepak; Sinha, Sarita; Rawat, Pratima; Afaq, Nashra; Kumar Patwa, Mukesh; Pal, Ashish; Abbas, Faisal; D Kandpal, Vikas (Journal of Neonatal Surgery, 2025)
Background: Colistin resistant K. pneumoniae has rapidly become one of the leading cause of nosocomial infection, community acquired infection and is major ongoing problem in the health care facilities globally, including India. Despite the critical importance of colistin as a last-resort antibiotic, limited studies have investigated colistin resistance in human infections. To bolster the number of so called “last resort” antimicrobial agents, polymyxins such as colistin are once again being administered clinically due to their potential effectiveness against MDR infections. Aim and Objective: To study the prevalence of MCR-1 gene and carbapenemase encoding genes among colistin-resistance Klebsiella pneumoniae in clinical isolates. Material and Methods: A total of 200 K. Pneumonia isolates were cultured and they were confirmed using the VITEK 2 system. The DNA was extracted using the Qiagen DNA extraction kit and the PCR was performed to detect the MCR-1 gene and Carbapenemase gene and the antibiotic susceptibilities, extended-spectrum beta-lactamase (ESβL), multidrug-re sistant (MDR), and CR-KP were determined by using the VITEK 2 system, disc diffusion, and the minimum inhibitory concentration (MIC) test according to the CLSI guidelines 2024. Result: In the present study out of 200 K. pneumoniae isolates it was noted that males were 111(55.5%) and females were 89 (44.5%) stating males were more in number, out of which carbapenem resistant K.pneumoniae were 50 (25%) in which males were 30(60%) and females were 20 (40%) and the colistin resistance percentage was 12.5 % (25/200).Shows the total number of isolates collected from samples in which urine (69%), blood(14%), pus (6.5%), sputum(5%), wounds(3.5%), tissue (1%), CSF (1%).In the present study the rates of ESβL, MDR, and CR-KP were observed to be 25%, 25% and 100%, respectively. It was noted that only one MCR-1 gene was expressed out of the 50 colistin resistance isolates was detected. Conclusion: The emergence of plasmid-mediated colistin resistance due to the mcr-1 gene poses a great threat to human health by causing the ineffectiveness of the last-resort antibiotic, polymyxins.